PENYELIDIKAN PENDUGAAN GEOLISTRIK UNTUK PENELITIAN AIR TANAH, DI ASRAMA RINDAM - SENTANI, KABUPATEN JAYAPURA, PROPINSI PAPUA - -, Geni Dipatunggoro; -, Yuyun Yuniardi (Bulletin of Scientific Contribution, 2013)
Geo-electric investigation is done at Asrama Rindam areal, Sentani Resort, Jayapura Regenc, Papua Province. The investigationis required to detection of rock and subsurface condition. Methode of geo-electric to support for groundwater investigation to use the soldier need at the Asrama Rindam, Sentani Resort, The vertical layer are layer-1 as the soil, layer-2 as tufaceous brecia, laye-3 as tufaseous sand, layer-4 as tufaseous brecia, layer-5 as volcanic brecia, layer-6 as tufaseous sand, and layer-7 as volcanic brecia. The rock layer groundwater potencial or reservoar are tufaseous sand at the 10 meter and 49 meter depth.